Compressional wave velocity and effective stress in unsaturated soil: Potential application for monitoring moisture conditions in vadose zone sediments. Issue 5 (4th August 2021) - Linneman, Dorothy C.; Strickland, Christopher E.; Mangel, Adam R.
Abstract: Compressional seismic (P‐wave) velocities were measured experimentally at different matric suctions and confining pressure states using a variety of sediments collected from the USDOE Hanford Site in southeastern Washington State. The P‐wave velocity was measured in variably saturated sediments using ultrasonic piezoelectric transducers, and matric suction was measured with a heat dissipation sensor. Desaturation of the samples occurred by means of evaporative drying. We propose a model to relate changes in P‐wave velocity to soil stress conditions using an effective stress formulation that includes capillary stress as well as adsorptive stress. We show that compressional wave velocities can be related to matric suction and confining stress using a model with five fitted parameters. A single set of parameters describing the relationship between effective stress and P‐wave velocity provide an excellent fit to data acquired on Hanford Formation samples. The results presented here suggest the utility of seismic methods for establishing low matric suction and flow conditions within variably saturated Hanford formation sediments, which could be applied at the field scale for evaluating the performance of environmental remediation efforts, such as soil desiccation and surface infiltration barriers. Core Ideas: Seismic velocity was measured for a range of matric suction values in Hanford soil. A new model including adsorptive forces relates P‐wave velocity and effective stress. This model can be applied to monitor changes in matric suction using seismic P‐wave velocities.